The Influence of system quality, information quality, service quality on user satisfaction - Henny Hamsinar; Mohammad Bukhori; Tin Agustina Karnawati (Jurnal Mantik, 2023)
Hence, the transformation towards the use of a modern and technology-based education system is important to answer the challenges and opportunities in the world of education today. Automate administrative and management processes, such as student registration, timetable management, and tracking academic progress. Utilization of modern systems not only provides administrative efficiency, but also helps construct a learning environment that is more inclusive and responsive. The aims of this study to verify and analyze the partial and simultaneous effect of system quality, information quality and service quality on student satisfaction as system users. The research sample taken was 63. The conclusion of this study showed that system quality (X1) had no effect on user satisfaction (Y) because t-count was smaller than t-table, videlicet 0.997 < 2.001 and was not significant because it had a significance value that was greater than 0.05 which is 0.328. Information quality (X2) has no effect on user satisfaction (Y) because the t-count is smaller than the t-table, videlicet 1.693 < 2.001 and is not significant because it has a significance value greater than 0.05, namely 0.102. Service quality (X3) has a significant influence on user satisfaction (Y) because t-count is greater than t-table, videlicet 5.731 > 2.001 and has a significance value smaller than 0.05, namely 0.000. Simultaneously system quality, information quality and service quality affect user satisfaction